Pengaruh Keterlibatan Karyawan, Stres Kerja, dan Komitmen Organisasi Terhadap Kepuasan Kerja Karyawan di PT. World Innovative Telecomunication Cabang Bengkulu - Belo Prayoga; M. Noor Army; Janusi Waliamin (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to find out how much influence employee involvement (X1), work stress (X2), and organizational commitment (X3) have on employee job satisfaction (Y) at PT. World Innovative Telecomunication Bengkulu Branch. Pemeltian is carried out with a quantitative approach through the explanator method. The research population of all employees at PT. World Innovative Telecomunication Bengkulu Branch totals 35 people sampling technique using total sampling where samples are taken by all employees working at PT. World innovative telecomunication Bengkulu Branch. Data was collected from respondents directly through questionnaires. The research data analysis technique used multiple linear regression, multiple correlation, determination coefficient, Ftest, and t-test. Based on the results of the study, (1) Employee involvement (X1) influences employee job satisfaction (Y) (2) Work stress (X2) has a negative effect on employee job satisfaction (Y) (3) Organizational commitment affects employee job satisfaction (Y) (4) There is a joint influence of independent variables on dependent variables where sig < α 0.05. Fcal > Ftable (16,373>3,34)